1995
DOI: 10.1146/annurev.ne.18.030195.001111
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Characterization, and use of Stem Cells from the CNS

Abstract: The nervous system of adult mammals, unlike the rest of the organs in the body, has been considered unique in its apparent inability to replace neurons following injury. However, in certain regions of the brain, neurogenesis occurs postnatally and continues through adulthood. The nature, fate, and longevity of cells undergoing proliferation within the CNS are unknown. These cells are increasingly becoming the focus of intense scrutiny; this is a recent development that has led to considerable controversy over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
231
0
3

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 779 publications
(236 citation statements)
references
References 82 publications
(81 reference statements)
2
231
0
3
Order By: Relevance
“…Woodbury et al (35) suggested that BMCs can differentiate into neural phenotypes in vitro. BMCs are likely to retain the capacity to respond to local epigenetic signals and to differentiate with a terminal phenotype appropriate for that ectopic site in the ischemic brain that represents a different environment than the intact CNS (11,36). Together, injected BMCs survived and were likely to differentiate into at least a modest number of neuronal and glial cell phenotypes in lesions, although it remains unclear how much they contributed to the behavioral rescue and improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Woodbury et al (35) suggested that BMCs can differentiate into neural phenotypes in vitro. BMCs are likely to retain the capacity to respond to local epigenetic signals and to differentiate with a terminal phenotype appropriate for that ectopic site in the ischemic brain that represents a different environment than the intact CNS (11,36). Together, injected BMCs survived and were likely to differentiate into at least a modest number of neuronal and glial cell phenotypes in lesions, although it remains unclear how much they contributed to the behavioral rescue and improvement.…”
Section: Discussionmentioning
confidence: 99%
“…The NSCs differentiate into neurons in regions undergoing neurogenesis or into glia, where gliogenesis is ongoing (6,24,25). Therefore, they emulate endogenous NSCs as well as NSC clones propagated by a variety of techniques from other structures (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). After 0-2 mitoses in the first 48 hr posttransplant, they become quiescent and intermingle nondisruptively with endogenous progenitors.…”
Section: Methodsmentioning
confidence: 99%
“…The recognition that NSCs, propagated in culture, could be reimplanted into mammalian brain, where they could reintegrate appropriately and stably express foreign genes (1)(2)(3)(4)(5)(6)(7)(8)(9), provided hope that their use might make feasible a variety of novel therapeutic strategies. When exogenous NSCs are transplanted into germinal zones, they circumvent the blood-brain barrier, migrate to distant CNS regions, and participate in the normal development of multiple regions throughout the brain and at multiple stages (from fetus to adult), integrating seamlessly within the parenchyma, differentiating appropriately into diverse neuronal and glial cell types.…”
mentioning
confidence: 99%
“…egenerative stem cells can be found in many adult tissues (1)(2)(3)(4)(5)(6). Although possessing substantial capacity to proliferate and differentiate, such cells are thought to be committed to differentiate exclusively into the tissues in which they reside.…”
mentioning
confidence: 99%